Wastewater biosolids: an overview of processing, treatment, and management. Issue 2 (1st March 2002) - Oleszkiewicz, J A; Mavinic, D S
Abstract : Treated as a valuable resource, municipal sludge, often today referred to as biosolids, is processed through a variety of novel unit operations leading to a safe, aesthetically pleasing, and sought-after product. The design engineer is concerned first with the ultimate disposal and utilization of the biosolids, providing at least two options for the final disposal. Volume reduction, stabilization or vector attraction reduction, and pathogen inactivation are the key goals; process trains combining them into one unit process are the target technologies. Drying and pelletization are now being applied at much smaller plants because of the introduction of indirect dryers, which have fewer air pollution problems than the direct dryers still used at some larger plants. Stabilization of biosolids in newer plants is more often combined with disinfection at thermophillic temperatures, in anaerobic and particularly in aerobic regimes. For the smallest plants, dewatering is now available in drying bags or vacuum drying beds, and larger plants benefit from an array of new devices offering sludge cakes as dry as 22 to 40% total solids. The ultimate dryness will depend on the quality of sludge, polymer conditioning program, and machine parameters. Emphasis on cost reduction, with simultaneous demand for an excellent quality end product, calls for innovative and case-specific solutions that go beyond the treatment plant and also address the quality of industrialcommercial discharges to the municipal sewers. Key words : sludge, biosolids, process design, dewatering, digestion.